A regulatory role for IL-4 in differential inflammatory responses in the lung following infection of mice primed with Th1- or Th2-inducing pertussis vaccines - MILLS, KINGSTON (My University, 2000)
Protection against infectious pathogens at mucosal surfaces is dependent on local antibody responses, production of inflammatory mediators, and recruitment of immune effector cells to the site of infection. Since Th1 and Th2 cells produce cytokines with pro- and anti-inflammatory activities, immunization with vaccines that induce these T-cell subtypes may regulate the subsequent inflammatory response to infection. We have demonstrated that immunization of mice with pertussis whole-cell or acellular vaccines (Pw or Pa) selectively induces Th1 and Th2 cells, respectively. In this study we have used a murine respiratory-infection model to demonstrate that priming with a Th1- or Th2-inducing pertussis vaccine can influence the local inflammatory response and immune effector cells in the lung following aerosol challenge with Bordetella pertussis. Analysis of bronchoalveolar lavage (BAL) fluid taken during the course of B. pertussis infection of naive mice or mice immunized with Pw revealed an early influx of neutrophils and local production of interleukin 1? (IL-1?) in the lungs. In contrast, neutrophil infiltration and IL-1? production were not observed following challenge of mice immunized with the Th2-inducing Pa. Conversely, during infection local production of IL-6 and IL-1ra was significantly greater in mice immunized with Pa than in those immunized with Pw. Studies of knockout mice revealed neutrophil and lymphocyte infiltration in the lungs following B. pertussis infection of IL-4-defective (IL-4?/?) mice but not in wild-type mice immunized with Pa. Furthermore, the levels of IL-1?, IL-6, and IL-1ra in Pa-immunized IL-4?/? mice were comparable to those in mice immunized with Pw. These results demonstrate distinct influences of Th1- and Th2-inducing vaccines on the protective inflammatory responses in the lungs following challenge with B. pertussis and implicate IL-4 as an important regulator of inflammatory-cell recruitment.
PUBLISHED
PMID: 10678951
Keywords: Biochemistry